2007
DOI: 10.2478/v10007-007-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vitro evaluation of buccoadhesive carvedilol tablets

Abstract: Buccal delivery of drugs provides an attractive alternative to the oral route of drug administration, particularly in overcoming deficiencies associated with the latter mode of administration. Problems such as high first-pass metabolism and drug degradation in the harsh gastrointestinal environment can be circumvented by administering the drug via the buccal route (1-3). Moreover, buccal drug absorption can be promptly terminated in case of toxicity by removing the dosage form from the buccal cavity. It is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Studies revealed that increasing the concentration of the polymer in the formulations showed a sustained effect on carvedilol release. The rapidly hydrating polymer dominated in controlling the release of carvedilol from the buccal tablets[31]. Propranolol hydrochloride (PRO-HCl), a nonselective beta-adrenergic blocking agent, has been widely used in the treatment of hypertension, angina pectoris, and many other cardiovascular disorders.…”
Section: A Clinical/therapeutic Approachmentioning
confidence: 99%
“…Studies revealed that increasing the concentration of the polymer in the formulations showed a sustained effect on carvedilol release. The rapidly hydrating polymer dominated in controlling the release of carvedilol from the buccal tablets[31]. Propranolol hydrochloride (PRO-HCl), a nonselective beta-adrenergic blocking agent, has been widely used in the treatment of hypertension, angina pectoris, and many other cardiovascular disorders.…”
Section: A Clinical/therapeutic Approachmentioning
confidence: 99%
“…Moreover, such type of delivery is considered to be safer since any time, drug absorption can be concluded if any toxicity occurs due to it by removing the formulation from the site of application. [12][13][14] . Thus, in the present research paper, buccal bio-adhesive tablet of nicorandil was prepared using a sustainedrelease polymer HPMC K100M 10,15 , bio-adhesive polymer neem gum 16 and an impermeable backing layer of ethyl cellulose.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…These bioadhesive polymers could also resist salivation, tongue movement, and swallowing for a significant period of time 29 . HPMC has been applied to formulate buccoadhesives of drugs like metronidazole, benzydamine, carvedilol, and so on 21,26 . The buccoadhesives of some drugs like metronidazole, benzydamine, prednisolone, and pindolol have been prepared by means of NaCMC as well 26,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various transmucosal routes, buccal mucosa has excellent accessibility that offers painless administration, easy drug withdrawal, fast onset of action, patient compliance, and attractive alternative for noninvasive delivery of some drugs [13][14][15][16][17][18][19][20] . The buccal region of the oral cavity is an attractive target for administration of the drug of choice 21 . Local delivery in the oral cavity has had particular applications in the treatment of toothache, periodontal diseases, and bacterial infections 22 such as toothpastes, mouthwashes, lozenges, gels, chewing gums, lollipops, films, patches, and tablets have developed for topical oral administration 19,23 .…”
Section: Introductionmentioning
confidence: 99%